ANALISIS PENIPUAN ONLINE DALAM BENTUK PHISING MENURUT PERSPEKTIF HUKUM INDONESIA - Nurfahda, Amanda Faizah; Jelita Putri, Annasyanda; Yardi, Nayottama Aryasuta; Deni, Fitra (SAHID BANKING JOURNAL, 2024)
The rapid flow of technology has brought so many impacts to various spheres of life, especially the rapid growth in the digital sphere. This technological development also brings a variety of positive contributions. However, along with the benefits, there are also new threats that need to be anticipated. Especially the threat of personal data leakage or misuse of data by irresponsible parties. This paper examines the phenomenon of cybercrime in the form of phishing from the perspective of Indonesian law. This paper uses normative juridical research methods. The researcher proves that phishing crime is a threat to the flow of digital development in Indonesia. Phishing crime no longer relies on one pattern, but comes in various motives and methods. Despite its various challenges and limitations, Indonesian law has been able to create a set of rules to tackle and anticipate phishing crimes.